2022
DOI: 10.3390/brainsci12050637
|View full text |Cite
|
Sign up to set email alerts
|

Finger-Based Numerical Training Increases Sensorimotor Activation for Arithmetic in Children—An fNIRS Study

Abstract: Most children use their fingers when learning to count and calculate. These sensorimotor experiences were argued to underlie reported behavioral associations of finger gnosis and counting with mathematical skills. On the neural level, associations were assumed to originate from overlapping neural representations of fingers and numbers. This study explored whether finger-based training in children would lead to specific neural activation in the sensorimotor cortex, associated with finger movements, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This supports the embodied representation of numbers and arithmetic operations in hands/fingers. In a recent study, Artemenko et al (2022) used a finger-based method for teaching arithmetic operations to a group of children. After 1 year of training, this group of children showed finger-related arithmetic effects accompanied by activation in the sensorimotor cortex during performing mental arithmetic operations.…”
Section: Transforming Representations and Embodimentmentioning
confidence: 99%
“…This supports the embodied representation of numbers and arithmetic operations in hands/fingers. In a recent study, Artemenko et al (2022) used a finger-based method for teaching arithmetic operations to a group of children. After 1 year of training, this group of children showed finger-related arithmetic effects accompanied by activation in the sensorimotor cortex during performing mental arithmetic operations.…”
Section: Transforming Representations and Embodimentmentioning
confidence: 99%
“…Employing EEG in 3-to-4-month-old infants, Decarli et al [ 8 ] found evidence for a neuro-functional link between numerosity processing and hand action processing. With the help of functional near-infrared spectroscopy (fNIRS) in a mental arithmetic training in first graders, Artemenko et al [ 9 ] were able to link the effects of a finger-based training on mental arithmetic (i.e., training-induced facilitation of subbase-5 carry operations) and the activation in the sensorimotor cortex in trained children, suggesting training-induced sensorimotor plasticity in brain development. Thus, the results of both studies support an embodied perspective on the representation of numbers already in early infancy.…”
Section: Typical Numerical Developmentmentioning
confidence: 99%